Competitive versus comparative advantage - J. Peter Neary (University College Dublin, Department of Economics, 2002)
I explore the interactions between comparative, competitive and absolute advantage in a two-country model of oligopoly in general equilibrium. Comparative advantage always determines the direction of trade, but both competitive and absolute advantage affect resource allocation, trade patterns and trade volumes. Competitive advantage in the sense of more home firms drives foreign firms out of marginal sectors but also makes some marginal home sectors uncompetitive. Absolute advantage in the sense of a uniform fall in home costs tends to raise home output in all sectors but also leads both countries to specialise less in accordance with comparative advantage.
hdl:10197/1325
Keywords: F10; F12; 330; Comparative and absolute advantage; comparative and competitive advantage; exchange-rate protection; GOLE (General Oligopolistic Equilibrium); market integration; Komparativer Kostenvorteil; Oligopol; Zwei-Länder-Modell; Allgemeines Gleichgewicht; Theorie